Neuronal connectivity between habenular glutamate‐kisspeptin1 co‐expressing neurons and the raphe 5‐HT system. (10th September 2015) - Nathan, Fatima M.; Ogawa, Satoshi; Parhar, Ishwar S.
Abstract: The habenula, located on the dorsal thalamic surface, is an emotional and reward processing center. As in the mammalian brain, the zebrafish habenula is divided into dorsal (dHb) and ventral (vHb) subdivisions that project to the interpeduncular nucleus and median raphe (MR) respectively. Previously, we have shown that kisspeptin 1 (Kiss1) expressing in the vHb, regulates the serotonin (5‐HT) system in the MR. However, the connectivity between the Kiss1 neurons and the 5‐HT system remains unknown. To resolve this issue, we generated a specific antibody against zebrafish Kiss1 receptor (Kiss‐R1); using this primary antibody we found intense immunohistochemical labeling in the ventro‐anterior corner of the MR (vaMR) but not in 5‐HT neurons, suggesting the potential involvement of interneurons in 5‐HT modulation by Kiss1. Double‐fluorescence labeling showed that the majority of habenular Kiss1 neurons are glutamatergic. In the MR region, Kiss1 fibers were mainly seen in close association with glutamatergic neurons and only scarcely within GABAergic and 5‐HT neurons. Our findings indicate that the habenular Kiss1 neurons potentially modulate the 5‐HT system primarily through glutamatergic neurotransmission via as yet uncharacterized interneurons. The neuropeptide kisspeptin (Kiss1) play a key role in vertebrate reproduction. We have previously shown modulatory role of habenular Kiss1 in the raphe serotonin (5‐HT) systems. This study proposed that the habenular Kiss1 neurons modulate the 5‐HT system primarily through glutamatergic neurotransmission, which provides an important insight for understanding of the modulation of 5‐HT system by the habenula‐raphe pathway. Abstract : The neuropeptide kisspeptin (Kiss1) play a key role in vertebrate reproduction. We have previously shown modulatory role of habenular Kiss1 in the raphe serotonin (5‐HT) systems. This study proposed that the habenular Kiss1 neurons modulate the 5‐HT system primarily through glutamatergic neurotransmission, which provides an important insight for understanding of the modulation of 5‐HT system by the habenula‐raphe pathway.